Application of Project-Based Learning Model to Enhance Creative Thinking Skills In Social Studies Learning For Students at MTS N 9 Agam - Sesriyenti, Trisna (LANGGAM: International Journal of Social Science Education, Art and Culture, 2023)
This study aims to obtain information and discuss the application of the Project-Based Learning model in enhancing students' creative thinking skills in social studies learning for Grade IX students at MTsN 9 Agam. The research employed a Classroom Action Research design with a qualitative approach conducted from January to June. The study consisted of three cycles, where Cycles I and II were conducted over three sessions, while Cycle III consisted of two sessions, following the planning, implementation, observation, and reflection procedures. The subjects of the study were 32 Grade IX students in class A at MTsN 9 Agam. Data were collected through learning outcome tests, student observation sheets, and field notes. The research findings revealed that the average number of students' creative thinking abilities during the teaching and learning process for the five indicators ranged from creative to highly creative. The students' learning outcomes showed an improvement in mastery, with 23 students (78.39%) achieving mastery in Cycle II, which increased to 26 students (86.49%) in Cycle III.